Analysis of Green Computing Implementation Strategies for Energy Efficiency in Server Infrastructure - Daniel Rionaldo; Alvin Leonardo Ishak (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The rapid development of information technology has increased the use of server infrastructure in various organizations and data centers, resulting in higher energy consumption and operational costs. Green computing is considered an effective approach to improve energy efficiency while reducing environmental impacts. This study aims to analyze green computing implementation strategies for improving energy efficiency in server infrastructure. The research used a descriptive qualitative method through literature studies and comparative analysis of energy management strategies in data centers. The strategies analyzed include server virtualization, server consolidation, energy-efficient hardware, and cooling system optimization. The results indicate that the implementation of green computing can significantly reduce energy consumption compared to conventional server systems. In addition, the implementation improves operational efficiency, reduces electricity usage, and supports environmentally sustainable data center management. Therefore, green computing can be considered an effective solution for developing efficient and environmentally friendly server infrastructure.